IDENTIFIKASI KERUSAKAN ANTROPOGENIK KAWASAN HUTAN LINDUNG MUTIS TIMAU DI PULAU TIMOR BAGIAN BARAT DAN UPAYA PENANGGULANGANNYA - Fransiskus Xaverius Dako; Ris Hadi Purwanto; Lies Rahayu Wijayanti Faida; Sumardi Sumardi (Graduate School Bogor Agricultural University (SPs IPB), 2019)
The life of humankind has a close relationship with its surrounding forests. The interaction /relationship is often in a lame and brings a negative impact on the forest. The impacts of these unbalanced relationships are the destruction of all production, conservation and protection areas of forests. This study aimed to identify the anthropogenic damages in Mutis Timau protected forest areas. This research was a qualitative research with a descriptive approach using a purposive sampling and a snowball sampling technique. The purposive sampling was used to select resource persons of the FMU chiefs, forest police staff, retired FMU employees and village heads where the samples were undertaken. While the snowball sampling technique was set according to a snowball pattern that began with the village leaders (village heads) and then progressed to other resource persons to obtain accurate information related to anthropogenic activities that caused forest destruction. The number of sources of informants were 62 people. Methods of data collection in this study include observation methods, indepth interviews and documentation. The preliminary research results indicate that the anthropogenic damages in Mutis Timau protected forest areas include forest encroachment, livestock grazing, shifting cultivation and forest fires, and illegal logging. Anthropogenic damage can be resolved by the management by involving community participation through joint forest management (collaborative) and can be conducted by using the social forestry systems